2016
DOI: 10.1123/pes.2015-0238
|View full text |Cite
|
Sign up to set email alerts
|

Maturity, Physical Ability, Technical Skill and Coaches’ Perception of Semi-Elite Adolescent Australian Footballers

Abstract: Purpose: To confirm the effect of maturational differences on anthropometric and physical testing and explore the effect of maturation on technical skill and coaches' perceptions of skill in adolescent Australian footballers. Methods: Athletes were recruited from a semi-elite under 16 competition (n = 94, age 15.7 ± 0.3 years) and completed anthropometric, physical, and technical skill tests. Coaches from each team provided subjective ratings of athletes' technical skills. Maturation groups were derived from y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 29 publications
3
46
0
1
Order By: Relevance
“…Gastin and Bennett [7] reported maturational differences between community U15 Australian footballers, however this is the first study to demonstrate that age-matched talent identified U16 Australian footballers are more mature than their non-talent identified counterparts. Between group variations in maturity reported in this study are likely to contribute to the anthropometric and physical performance differences demonstrated between the talent identified and non-talent identified groups, as players of advanced maturational age are typically taller, heavier and have been shown to possess greater vertical leaps than their less mature counterparts [7,9,19]. Maturational variation has previously been shown to account for between 8-19% of physical performance variability and affect coaches' perceptions of skill and potential in U16 Australian footballers [9,10].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Gastin and Bennett [7] reported maturational differences between community U15 Australian footballers, however this is the first study to demonstrate that age-matched talent identified U16 Australian footballers are more mature than their non-talent identified counterparts. Between group variations in maturity reported in this study are likely to contribute to the anthropometric and physical performance differences demonstrated between the talent identified and non-talent identified groups, as players of advanced maturational age are typically taller, heavier and have been shown to possess greater vertical leaps than their less mature counterparts [7,9,19]. Maturational variation has previously been shown to account for between 8-19% of physical performance variability and affect coaches' perceptions of skill and potential in U16 Australian footballers [9,10].…”
Section: Discussionmentioning
confidence: 85%
“…Poor retention of juniors may be linked to the relative age effect repeatedly reported in adolescent competitions [6,12,13], which suggests that older players are looked upon more favourably in the initial identification process due to maturational advantage. This suggestion is supported by recent findings that Australian football coaches' perceive earlier maturing individuals to possess advanced technical skills and greater long-term potential [9,10]. However, despite these findings there is no available research exploring factors which drive identification into the AFL TP at the U16 level.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The study of the traditional sport TID [11] also emphasized that the potential and talented athletes who often drop out because of the TID concept that does not fit. Currently, findings demonstrated coaches' perceptions of long-term potential can be biased by maturational variation in adolescent athletes [5]. Such perceptual bias may impact on coaches selection decisions and result in talented but late maturing athletes missing selection into development pathways.…”
Section: Introductionmentioning
confidence: 99%